Assessment of the stability of mephedrone in ante-mortem and post-mortem blood specimens. (November 2015) - Busardò, Francesco Paolo; Kyriakou, Chrystalla; Tittarelli, Roberta; Mannocchi, Giulio; Pantano, Flaminia; Santurro, Alessandro; Zaami, Simona; Baglìo, Giovanni
Highlights: −20 °C is the best storage temperature among the ones tested. Ante-mortem samples are more stable than post-mortem at all tested conditions. NaF/KOx maintains mephedrone's stability better than EDTA or no preservative. Abstract: Aims: The aim of this work is to test the stability of mephedrone added to whole blood collected from alive and dead mephedrone free-users and stored at three different temperatures (−20, +4 and +20 °C) with and without preservatives up to 6 months, trying to establish the best storage condition in order to reduce possible analyte loss/degradation during the storage period. Materials and methods: Different sources of blood were obtained as follow: 10 samples of blood came from 10 alive mephedrone free-users (mean age 34 ± 15.8 years old) (Group 1), whereas 10 post mortem blood samples were obtained from 10 cadavers, in which the post mortem interval was between 24 and 36 h (Group 2). The cause of death in post mortem cases (mean age 45 ± 14.2 years old) was not drug related. Pools of blood were spiked with mephedrone at the concentration of 1 mg/L and 1 mL aliquots were transferred in 2 mL Eppendorf capped tubes with and without preservatives as follow: with ethylenediaminetetraacetic acid (EDTA) 3%; with sodium fluoride/potassium oxalate (NaF/KOx) 1.67%/0.2%, respectively; without preservatives. All samples were stored at three different temperatures: −20 °C, 4 °C and 20 °C and extracted and analyzed in duplicate by GC–MS according to a previously published method by Dickson et al., every other day during the first month and then weekly up to 6 months. Results and conclusions: our study allow us to affirm that −20 °C is the best storage temperature for mephedrone stability in ante-mortem and post-mortem blood samples in comparison to the other two tested temperatures (+4 and +20 °C), showing higher values in both groups in samples stored with and without preservatives ( p  < 0.0001). The comparison of Group 1 (samples coming from alive subjects) and Group 2 (post-mortem samples) highlights a better stability of mephedrone in Group 1 ( p  < 0.001) at all tested storage conditions. Finally, the analysis of blood specimens stored with and without preservatives in both groups suggests that specimens stored with NaF/KOx maintain mephedrone stability better than those stored with EDTA ( p  < 0.001) and those stored without preservatives ( p  < 0.0001), therefore, we strongly recommend in order to maintain the highest mephedrone stability in blood, to store specimens at −20 °C adding NaF/KOx as preservative.